Breast Reconstruction with a Lateral Breast Free Flap: A New Application of Breast-sharing. Issue 3 (24th March 2020) - Lopez, Carlos E.; Caicedo, Jose J.; Pizano, Alejandro; Hoyos, María E.
Abstract : Supplemental Digital Content is available in the text. Abstract : Summary: Breast reconstruction using contralateral autologous tissue, also known as breast sharing, is a viable option previously described in the literature, whereby flaps based on perforators of the internal mammary artery (internal mammary artery pedicle) are used. We report a postoncological breast reconstruction case using a microvascular flap taken from the lateral pole of the contralateral breast. We highlight the importance of preserving the medial pole of the donor breast for improving cosmesis, avoiding symmastia, and preserving the intermammary sulcus, as a difference with flaps based on the internal mammary artery pedicle flaps. Breast sensation could be recovered by neurotization of the lateral intercostal nerve, which may be included in the contralateral breast flap to be transferred. Contralateral breast free flaps could be an alternative to reconstruct the breast in selected patients. Oncological risk factors are discussed. Advances in genetic testing and tumor cell biology could help us to select the accurate candidates for this reconstructive technique.